The Stone Age in a Space Cruiser - Wulf Hein (EXARC Journal)
The Jeongok Prehistory Museum in South Korea. Like a stranded UFO the building is settled between the hills at a river (See Figure 1), the sun reflects off the metal outer skin. Standing in the entrance area, you feel as though you are in a film by Stanley Kubrick, but as you pass through into the structure it is a surprise to find yourself outside in the middle of the African savannah, surrounded by prehistoric people and all kinds of animals. The new Prehistory Museum in the north of South Korea unites futuristic architecture with the archaeology of humankind in an elegant way and attracts a million visitors yearly with its charm.